“Changing Gears” A Comparative Study of Male and Female Preference for Two-Wheeler in Palghar District of Maharashtra (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Women play a significant role in driving the econ omy of the world. Companies that sell to both  men and women have always had larger market  share. In India the number of female Two-wheeler  users is rising very rapidly and the overall de mographic profile of the Two-wheeler users has  undergone a drastic change. The Two-wheeler is  considered to be the most convenient and eco nomical mode of transportation. The COVID  crisis has further helped in giving a boost to the  sales of Two-wheeler as people would now reduce  their dependency on the public means of trans portation. This has created a huge opportunity for  the Two-wheeler companies. In India Two-wheeler  manufacturing companies indulge in aggressive  marketing techniques and launch new models  with latest technology to impress the customer.  Internet now is considered as a vital medium of  communication with the customers as more and  more people; especially the young are hooked to  the internet. The study tries to analyse the influ ence of internet on the users of the Two-wheeler  and the impact of celebrity endorsement on the  buying decisions. The research undertaken makes  an attempt to understand the preferences of male  and female Two-wheeler users and the important  factors that motivate buyers to choose a particular  brand of Two-wheeler. The study explains certain  factors, which the consumers consider more significant as compared to other factors. It hopes to shed  light on the role of family members and friends  on the buying decisions. An attempt is made to  analyse the changing consumer behaviour with  reference to buying a Two-wheeler. The research  aims to find the most preferred Two-wheeler  brand in Palghar district. The study undertaken  will provide new insights into the aspects that  are considered most significant by Two-wheeler  users irrespective of the gender thereby helping  managers making better decisions that will lead to  attracting more customers. The implementation  of the suggestion proposed at the end of the study  will hopefully result in higher levels of customer  satisfaction. The research is significant as it hopes  to lay a foundation for further studies on similar  lines which can be replicated in other parts of the  country. It will also provide new insights and help  look at things from the perspective of the buyer
Keywords: Two-wheeler; respondents; district; male; female